How to Write a Letter to the Editor? - Ebrahim Piri; AmirAli Jafarnezhadgero (Islamic Azad University, Hamedan Branch, 2023)
A Letter to the Editor (LTE) is a brief communication to a journal's editor or editorial team. It is usually written in response to a recent publication within the journal but can also cover an unrelated topic of interest to the journal's readership. Many journals welcome LTEs within a dedicated section (e.g. LTEs/Correspondence) to stimulate intellectual discussions between readers and authors. LTEs may be handled by a dedicated 'LTE' team. Therefore, in this article, our aim is to provide practical tips on writing a successful LTE.